2010
DOI: 10.3844/ajassp.2010.371.375
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Penetration Resistance Studies on Concretes Modified with Alkali Resistant Glass Fibers

Abstract: Problem statement: This research study presented the durability performance of glass fibre reinforced concrete. Approach: The influence of fiber content on the durability performance of glass fibre reinforced concrete specimens having different percentage of glass fibres with varying grades of concrete were investigated. Results: The parameter of investigation included rapid chloride permeability test for a period of 365 days. Specimens of 100×150 mm cylinders were cast and tested to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The durability of different AR-GFRC was investigated by Bentur and Bassat [9]; the aging effects on the flexural properties and the microstructure of the composites were determined in different environments and the test results were verified by scanning electron microscopy (SEM). Chandramouli, Rao, et al [10] investigated the durability of concrete specimens with different fiber content using a rapid chloride ion penetration test; the effect of the glass fiber content on the concrete durability and strength was determined. As new techniques have been developed, nondestructive testing methods have been used to monitor the aging process of GFRC.…”
Section: Introductionmentioning
confidence: 99%
“…The durability of different AR-GFRC was investigated by Bentur and Bassat [9]; the aging effects on the flexural properties and the microstructure of the composites were determined in different environments and the test results were verified by scanning electron microscopy (SEM). Chandramouli, Rao, et al [10] investigated the durability of concrete specimens with different fiber content using a rapid chloride ion penetration test; the effect of the glass fiber content on the concrete durability and strength was determined. As new techniques have been developed, nondestructive testing methods have been used to monitor the aging process of GFRC.…”
Section: Introductionmentioning
confidence: 99%
“…Significant studies have been conducted to improve the tensile characteristics of such cementitous materials. Several of these investigations focused on the inclusion and effect of discontinuous reinforcement, emphasizing the influence of short, randomly distributed fibers on concrete's tensile characteristics (Banthia and Gupta, 2004;Ravichandran et al, 2009;Ramli, 2010;Chandramouli et al, 2010). The experimental and analytical results revealed that the addition of discontinuous fibers to the cementitious matrix can have a significant influence on post-crack ductility and greatly improves toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization of NaCl salt inside these microfissures may have favored the breakdown the mass of proof bodies containing the compound. Some of the solutions to decrease the permeability of chloride in mortar may be the incorporation of bagasserice husk-wood ash like additive (Horsakulthai and Paopongpaiboon, 2013) and the incorporation of alkali resistant glass fiber, according Chandramouli et al (2010). By means of the data obtained in the ultraviolet tests, shown in Table 3, it was found that the loss of mass by mortar containing the residue dregs-grits were similar to standard mortar.…”
Section: Resultsmentioning
confidence: 96%